Disponibilidade de fósforo avaliada por distintos extratores em função da calagem em solos do Paraguai - Fornasari, Carlos Henrique (2024)
In Paraguay, there are few studies to evaluate the availability of phosphorus in the soil, using extractants other than the double acid Mehlich-1 (M-1). However, doubt arises regarding the possibility of using results from calibration work carried out in other locations around the world. It is noteworthy that both the Mehlich-3 extractor (M-3) and the anion exchange resin (RTA) have not yet been evaluated as possible routine methods for determining P in soils representative of the country. Thus, the objectives of the work were to evaluate the availability of phosphorus in different soils in Paraguay by extractors M-1, M-3 and RTA and the sensitivity of these extractors to liming and also calculate the critical levels of P obtained for these extractors. The experiment was conducted from May to September 2023, in a greenhouse, in Hernandarias, Paraguay. Plastic pots with drainage holes and a capacity of 3.0 dm-3 were used, filled with soil samples (Lixisol, Gleysol, Oxisol, Nitisol and Planosol). For each type of soil, treatments were generated by combining a 4x2 factorial, with four doses of phosphorus (0, 50, 150 and 300 mg kg-1 of P) and two soil acidity conditions (with liming and without liming). A completely randomized experimental design was used, with four replications. Corn (Zea mays L.) was used as a reference plant species, with four plants per pot, cultivated for 45 days. At the end of the experiment, the production of dry matter, the content and accumulation of phosphorus in the aerial part of the plants and the levels of available P in the soil were determined, evaluated by extractors M-1, M-3 and RTA. Regression equations were adjusted for the effects of P doses and correlation between variables. Furthermore, critical P levels were determined for each type of soil studied. The extraction solutions M-1, M-3 and RTA proved to be effective in estimating phosphorus availability in soils in Paraguay, with high correlation coefficients between the extracted phosphorus and its content in the aerial part of corn plants. Liming influenced phosphorus recovery at doses of 300 mg kg-1, being observed for M-3 in Oxisol and Planosol, M-1 in Gleysol and Planosol, and RTA in Gleysol, Oxisol and Planosol. However, there was no effect of liming for M-3 in Gleysol, Lixisol and Nitisol, M-1 in Oxisol, Lixisol and Nitisol, and RTA in Lixisol and Nitisol. The critical phosphorus levels, ordered quantitatively for the five soils, followed the sequence: M-3 > RTA > M- 1.